2017
DOI: 10.1007/s12011-017-1094-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Selenium-Enriched Probiotics Enhances Meat Quality of Broiler Chickens (Gallus gallus domesticus) Raised Under High Ambient Temperature

Abstract: We investigated the effects of selenium-enriched probiotics (SP) on broiler meat quality under high ambient temperature and explore their underlying mechanisms. A total of 200 1-day-old male broiler chicks (Ross 308) were randomly allotted to four treatment groups, each with five replicates, in groups of ten birds. These birds were fed a corn-soybean basal diet (C), a basal diet plus probiotics supplementation (P), a basal diet plus Se supplementation in the form of sodium selenite (SS, 0.30 mg Se/kg), and a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 33 publications
4
24
2
1
Order By: Relevance
“…Wolter et al (1999) and Boiago et al (2014) reported that there was no significant difference in shear force and cooking loss regardless the source or the concentration of Se used [38,39]. However, Khan's et al (2018) research showed that adding Se-enriched probiotics could reduce the shearing force of breast muscle and improve muscle tenderness in broiler [40], which is consistent with the results of this experiment. It can be concluded that organic Se had a better effect on improving meat quality than inorganic Se.…”
Section: Discussionsupporting
confidence: 83%
“…Wolter et al (1999) and Boiago et al (2014) reported that there was no significant difference in shear force and cooking loss regardless the source or the concentration of Se used [38,39]. However, Khan's et al (2018) research showed that adding Se-enriched probiotics could reduce the shearing force of breast muscle and improve muscle tenderness in broiler [40], which is consistent with the results of this experiment. It can be concluded that organic Se had a better effect on improving meat quality than inorganic Se.…”
Section: Discussionsupporting
confidence: 83%
“…Jin et al (2018) also did not observe the effect of chromium methionine (200 µg/kg) in parameters of color. Dn the other hand, Khan, et al (2018), using 0.3 mg/kg of sodium selenite, observed increased in a* and b* in poultry, in discordance with our finds.…”
Section: Display Lifecontrasting
confidence: 81%
“…The drip loss at 48 hours was lower (p = 0.013) for the animals' meat that received MgSe than those supplemented with CrFe, however, both groups did not differ from the control group and this presented similar means to CrFeMgSe (Table 2). Khan et al (2018) demonstrated that supplementation of broilers with 0.30 mg Se/kg in the form of sodium selenite, increased the water hold capacity and the glutathione peroxidase (GSH-Px) activity. Selenium is an integral part of various selenoproteins, and it is possible to mention the selenoprotein W (Sel W) which has demonstrated present antioxidant activity dependent on GSH-Px and contrary to the other selenoproteins, its expression in the muscle is increased even in cases of excessive selenium consumption (Jeong et al, 2004).…”
Section: Physical-chemical Characteristicsmentioning
confidence: 99%
“…Probiotics are usually given orally, therefore the strains must have the ability to survive passage through stomach and duodenum where pH is low and bile is added. Therefore, resistance to the low pH, tolerance to bile salt are considered important properties of beneficial microbes (Yadav et al, 2016;Khan et al, 2018). All the isolated strains were able to tolerate pH (02-08) and presence of bile salt (0.5-2.0%) even for 24 hours of incubation at 37 o C. NaCl is an inhibitory substance which inhibit growth of many types of bacteria, therefore high salt tolerance is considered as a criteria of probiotic property.…”
Section: Discussionmentioning
confidence: 99%